Complete Genome Sequence of Escherichia coli MT102, a Plasmid-Free Recipient Resistant to Rifampin, Azide, and Streptomycin, Used in Conjugation Experiments - Valcek, Adam; Overballe-Petersen, Søren; Hansen, Frank; Dolejska, Monika; Hasman, Henrik (Microbiology resource announcements, 2019)
We present here the complete genome sequence of Escherichia coli MT102, which is resistant to rifampin, azide, and streptomycin and is used as a recipient in plasmid transfer experiments. The sequence will be utilized for chromosomal read removal in plasmid sequence analyses obtained from transconjugants within this strain and in comprehensive genetic studies.